Khrōngkān wičhai phư̄a tittām læ pramœ̄̄nphon kāndamnœ̄nngān khō̜ng thīm witthayākō̜n būranākān bambat raksā yāsēptit čhangwat - Kānčhanā Bunsong (Samnakngān Pō̜.Pō̜.Sō̜., Krasūang Yuttitham, 2007)
Research report on monitoring evaluation programme for follow-up the key operating teams of Integrated Treatment and Care of the drug dependents in nine pilot provinces in the four regions of Thailand.